Effect of zinc oxide (ZnO) nanoparticles on morphological traits, yield and uptake in tomato (Solanum lycopersicum) and bell pepper (Capsicum annuum) - BHARDWAJ, GITIKA; BRAR, PERMINDER SINGH; CHAUHAN, ANJALI; KAUSHAL, RAJESH; SHARMA, UDAY (The Indian Journal of Agricultural Sciences, 2025)
Zinc, an essential micronutrient, is extensively studied for its potential application as a nano-fertiliser in agriculture. Zinc oxide (ZnO) nanoparticles are known to boost root contact and nutrient mobilisation in the rhizosphere by releasing bioavailable Zn2+ ions, improving nutrient uptake and overall plant vigour. The present study was carried out for two consecutive years during rainy (kharif) season of 2020–22 at Dr Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to investigate the optimum concentration of zinc as nano-fertiliser by examining its effect on morphological characteristics, yield and nutrient uptake in tomato (Solanum lycopersicum L.) and bell pepper (Capsicum annuum L.). The pot experiments comprised of seven treatments set up in a completely randomised design (CRD) with three replications for both crops. Treatment combinations consisted of three concentrations of ZnO nanoparticles i.e. 50, 100, and 150 mg/L; which was applied as seed treatment [T2 (50 mg/L), T4 (100 mg/L) and T6 (150 mg/L)] and foliar application [T3 (50 mg/L), T5 (100 mg/L) and T7 (150 mg/L)] with T1 taken as control. Recommended dose of nutrients was applied, through integration of vermicompost and chemical fertilisers. ZnO nanoparticles @50 mg/L through foliar spray significantly enhanced various growth attributes as compared to control, viz. plant height (28% and 65%), root length (67% and 71%), number of primary branches, plant biomass, fruit yield (approx. 2–3 fold increase) and nutrient uptake in tomato and bell pepper, respectively. Whereas, seed treatment @50 mg/L significantly increased nutrient content in plants. Overall, the results concluded that application of ZnO nanoparticles @50 mg/L emerged as a promising nano-fertiliser strategy for enhancing morphological traits, yield and uptake in tomato and bell pepper.